You are on page 1of 2

) (

:
x a e x ln
:
ex > 0

"r

"x

ex e y = ex + y

ln e x = x
["x ]0; +
eln x = x

["y ]0; +

" ( x; y )
= erx

"x

) (

1
= e- x
x
e

e x = y x = ln y

" ( x; y )

ex = ey x = y

ex

x-y

ex > e y x > y

:
f
f ( x ) = ex

=e

ex
ey

= Df

} Df = {x / x D u

u x
) ( f (x) = e

:
:

u x
lim u ( x ) = + lim e ( ) = +

lim e x = +

x +

x x0

u x
lim u ( x ) = - lim e ( ) = 0

lim e x = 0

x -

= +

ex
xn

lim

x +

x x0

)* ( n

lim x n e x = 0

x -

ex - 1
lim
=1
x 0 x

= +

u x
) ( e
n

u ( x )

x x0

x x0

lim u ( x ) = + lim

x x0

x x0

n u x
lim u ( x ) = - lim u ( x ) e ( ) = 0
xx
x x
0
)u(x

-1
= +
)u(x

lim u ( x ) = 0 lim

x x0

x x0

x 0 x 0
+ -

:
x a e x

u x
u I ) ( x a e I

24


x a e x

"x
e x = e x :

u I

) ( x a e I
u x
u x
"x I
e ( ) = u ( x ) e ( ) :
u x

) (

aa *+ - {1} :
:
x a a x log a a

:
" ( x; y )

"x

a x = e xln a

) (

ax ay = ax+y

log a a x = x
x

a log a = x

= a rx

["x ]0; +

ax = ay x = y
["x "y ]0; +

) (a

x r

1
= a -x
x
a

) a x = y x = log a ( y

= ax-y

ax
y

:
0 < a <1
ax > ay x < y

a >1
ax > ay x > y

lim a x = 0

lim a x = +

x +

x +

lim a = +

lim a x = 0

x -

x -

a -1
= ln a
x 0
x
x

lim

:
x

( a ) = ( ln a ) a
x

25

)( r